2011
DOI: 10.1186/1471-244x-11-195
|View full text |Cite
|
Sign up to set email alerts
|

Family structure and posttraumatic stress reactions: a longitudinal study using multilevel analyses

Abstract: Background: There is limited research on the relevance of family structures to the development and maintenance of posttraumatic stress following disasters. We longitudinally studied the effects of marital and parental statuses on posttraumatic stress reactions after the 2004 Southeast Asian tsunami and whether persons in the same households had more shared stress reactions than others. Method: The study included a tourist population of 641 Norwegian adult citizens, many of them from families with children. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
(68 reference statements)
0
10
1
Order By: Relevance
“…Those who were required to make decisions within close relationships seemed to have a risk to PTSD, because ''self'' and ''not married'' in 'dominant role in spousal relationship' displayed high scores as well as ''try to organize'' in 'predominant forms of response in stressful situation.' Although the impact of marital status on PTSD was previously reported to be ambiguous [32], ''not married'' was associated with high scores in the present study. Adults living in the same household reported sharing similar PTSD levels [33], but the level also seemed to be dependent on 'role in spousal relationship.'…”
Section: Discussioncontrasting
confidence: 71%
“…Those who were required to make decisions within close relationships seemed to have a risk to PTSD, because ''self'' and ''not married'' in 'dominant role in spousal relationship' displayed high scores as well as ''try to organize'' in 'predominant forms of response in stressful situation.' Although the impact of marital status on PTSD was previously reported to be ambiguous [32], ''not married'' was associated with high scores in the present study. Adults living in the same household reported sharing similar PTSD levels [33], but the level also seemed to be dependent on 'role in spousal relationship.'…”
Section: Discussioncontrasting
confidence: 71%
“…Additionally, partners of individuals with PTSD often experience considerable psychological distress (e.g., Jordan et al, 1992). Nygaard and colleagues (2011) found that following a trauma, cohabitating individuals showed more similar PTSD symptoms than non-cohabitating individuals, and concluded that one's reactions to trauma may impact his/her partner's PTSD symptoms over time, though partners' PTSD symptoms may be more consistent with generalized distress than PTSD-specific symptoms (Renshaw et al, 2011). The degree of general distress present in a sample is not commonly considered in studies of the PCL-S's diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…A bivariate overview of all relationships was performed with Pearson’s correlation, and the bivariate mean differences between multiple groups were assessed with one-way ANOVA. Because study participants were partly clustered together in families with shared households, we applied mixed effects linear regression analyses [ 28 ]. All multiple mixed effects models controlled for gender, age, exposure, perceived threat of death, loss and social support.…”
Section: Methodsmentioning
confidence: 99%